MAKNA MODERASI BERAGAMA BAGI MAHASISWA: ANTARA IDEALISME NORMATIF DAN REALITAS SOSIAL DI PTKIN - Untsa Islami Kunana (Makkah: Journal Of Islamic Studies, 2025)
This study aims to explore how students at State Islamic Higher Education Institutions (PTKIN) in Indonesia interpret the concept of religious moderation within their academic and social lives. Religious moderation is a strategic policy discourse promoted by the Ministry of Religious Affairs to cultivate tolerant, inclusive, and balanced religious attitudes amid growing symptoms of intolerance and radicalism. However, the meaning of this concept among students has not been thoroughly investigated from the perspective of their subjective experiences. Therefore, this research adopts a phenomenological qualitative approach to capture students’ understanding, interpretations, and lived experiences in responding to the institutionalized values of moderation. Data were collected through in-depth interviews, participatory observation, and document analysis involving students from diverse backgrounds at three PTKIN campuses in Indonesia. The findings reveal that students’ understanding of religious moderation is pluralistic and shaped by their educational backgrounds, affiliations with student organizations, and exposure to social media. There exists a tension between the normative idealism promoted in academic settings and the social realities of student life, which are often characterized by ideological polarization, resistance, and communal dynamics. While some students perceive moderation as a noble value worth embodying, others view it with skepticism, seeing it as a political tool of the state that may not genuinely reflect their lived needs and experiences. The study concludes that internalizing the values of religious moderation in PTKIN environments requires a more contextual, dialogical, and experience-based approach. These findings are expected to enrich the discourse on strengthening religious moderation in Islamic higher education and to serve as a reference for future policy evaluation and value-education strategies.